Genetic inheritance of fruit traits and seed coat colour in bitter gourd (Momordica charantia) - RAO, P GANGADHARA; BEHERA, TUSAR KANTI; MUNSHI, ANILABH DAS; JAT, GOGRAJ SINGH; G, BOOPALAKRISHNAN (The Indian Journal of Agricultural Sciences, 2022)
The present experiment on genetic inheritance of fruit traits (ridgeness, tubercles and curviness) and seed coat colour of bitter gourd (Momordica charantia L.) was carried out at experimental farm of Division of Vegetable Science, ICAR-IARI, New Delhi in 2014–16. The study provides genetic information for development of new varieties and hybrids as per the consumer preference. The classical Chi-square (χ2) test was used to estimate the inheritance pattern of qualitative traits using six generations (P1, P2, F1, F2, BC1P1 and BC1P2; F3 generation as F2 for seed coat colour). Inheritance of fruit traits like continuous ridges (Cr: in DBGS-54 × DBGS-2 and DBSS-54 × Pusa Vishesh; χ2 = 0.09; P = 0.76 and χ2 = 0.50; P = 0.48, respectively), tubercles (Tb: DBGS-54 × DBGS-2 and DBSS-54 × Pusa Vishesh; χ2 = 0.50; P = 0.48and χ2 = 0.01; P = 0.92, respectively), fruit curviness (Cf: DBGS-54 × DBGS-2; χ2 = 0.02; P = 0.89) and black seed coat colour (Bs: Pusa Aushadhi × DBGS-54 and DBGS-54 × DBGS-2; χ2 = 0.73; P = 0.39 and χ2 = 0.02; P = 0.89, respectively) were found to be controlled by single dominant gene. Simple inheritance of these fruit traits will enable the bitter gourd breeder to incorporate these traits in hybrids. The black seed coat colour will act as a morphological marker for hybrid seed purity test too.